Combined congenital aortic stenosis and coarctation of aorta with severe left ventricle dysfunction and pulmonary hypertension in an infant-one case, multiple challenges - Sharma, Sourabh; Sharma, Kritika; Katkade, Sandip (International Journal of Research in Medical Sciences, 2024)
Aortic stenosis (AS) is commonly associated with coarctation of aorta (COA). Due to chronic increase in afterload, it can lead to left ventricle (LV) dysfunction and ultimately LV failure. We present a case of 10-month-old infant with combined AS and COA, complicated by severe LV dysfunction and severe Pulmonary hypertension (PH). There are no guidelines as to which condition should be treated first although both staged and combined procedure have been reported. It poses multiple challenges in the perioperative management. Although performing a balloon aortic valvuloplasty first would reduce the surgical risk for COA repair significantly, but due to lack of facilities for same in this age group, we proceeded with a high-risk COA repair via thoracotomy, avoiding the need for cardiopulmonary bypass (CPB). Application of Aortic cross clamp was associated with a further increase in afterload and hypotension owing to severe LV dysfunction in contrast to the expected increase in proximal pressures, and required high inotrope support to manage hemodynamics. Postoperative course was challenging as well owing to severe pulmonary hypertension. Very few similar cases have been reported in literature.